Little Red Riding Hood - Davidson, Susanna; Illustrated by Mike Gordon (London Usborne, 2006)
A beloved fairy tale, retold for young children in classic picture book format. Arriving at Granny's cottage, Little Red Riding Hood can't help but wonder why Grandma has such big eyes, ears and teeth. Could it be something to do with the wolf her mum told her not to talk to on the way?
Include color Illustrations
Keywords: Little Red Riding Hood (Tale) -- Wolves -- Folklore